Radiation Dose Assessment In Torso Phantom From Spect-CT Imaging - Rahman, Siti Fairus Abdul (2016)
Single Photon Emission Computed Tomography-Computed Tomography (SPECT-CT) systems are one of the latest technologies that have been used regularly in nuclear medicine imaging because of their ability to provide precise localisation of the anatomical images and physiological data from nuclear medicine studies. However, the exposure to radiation especially x-rays pose risk of inducing cancer in patients. Therefore, quantifying the radiation dose from SPECT-CT imaging was the main aim of this study in order to ensure that patients are exposed to minimal amount radiation.